2011
DOI: 10.1126/scitranslmed.3002011
|View full text |Cite
|
Sign up to set email alerts
|

Broken Barriers: A New Take on Sepsis Pathogenesis

Abstract: Despite intense research into the pathogenesis of sepsis, the current therapy for this devastating syndrome is primarily supportive and mortality remains high. The paucity of specific therapies is not for lack of effort; countless clinical trials in sepsis patients have failed despite promising preclinical data obtained from in vitro and animal models. Human sepsis is characterized by diffuse microvascular leak and tissue edema-features that have been largely ignored in animal models. Moreover, there have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
247
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(262 citation statements)
references
References 44 publications
3
247
0
3
Order By: Relevance
“…Cytokine levels are known to be temporally regulated in response to infection, and we might have missed the peak levels in proinflammatory cytokine expression typically observed in the first few hours following immune insult (40). Moreover, the significantly high expression of the antiinflammatory cytokine IL-10 suggests altered expression and distribution of cellular junction proteins (18,33). Increased vascular permeability in our model was accompanied by reduced expression of tight junction proteins occludin a and b, claudin 5a and b, and their intracellular partner ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine levels are known to be temporally regulated in response to infection, and we might have missed the peak levels in proinflammatory cytokine expression typically observed in the first few hours following immune insult (40). Moreover, the significantly high expression of the antiinflammatory cytokine IL-10 suggests altered expression and distribution of cellular junction proteins (18,33). Increased vascular permeability in our model was accompanied by reduced expression of tight junction proteins occludin a and b, claudin 5a and b, and their intracellular partner ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…A severe complication of pneumonia is systemic spreading of the invading pathogen finally resulting in acute respiratory distress syndrome (ARDS), septic shock and sepsis [37][38][39]. A plethora of clinical studies has shown that pathogenesis of ARDS and sepsis include the influx of protein-rich fluid into the air spaces as a consequence of increased permeability of the blood-air barrier leading to fatal lung edema formation [40][41][42][43]. Experimental studies in animals and cultured cells strengthened the hypothesis that junctional disruption of the lung barrier significantly contributes to a deleterious outcome [44][45][46].…”
Section: Pneumoniamentioning
confidence: 99%
“…Proinflammatory reactions are thought to be responsible for collateral tissue damage in severe sepsis such as dysfunction of the vascular endothelium, accompanied by cell death and loss of barrier integrity, giving rise to subcutaneous and bodycavity edema. 91 Further several factors (hypotension, reduced red-cell deformability and microvascular thrombosis) contribute to diminished oxygen delivery in septic shock. 92 As well known, the major pathophysiologic changes in patients with severe sepsis and septic shock include vasoplegic shock (distributive shock), myocardial depression, altered microvascular flow, and a diffuse endothelial injury.…”
Section: Septic Shock: Pathophysiology and Hemodynamic Resuscitationmentioning
confidence: 99%